Parity moderates the effect of delivery mode on maternal ratings of infant temperament - Takács, Lea; Putnam, Samuel P; Bartoš, František; Čepický, Pavel; Monk, Catherine (PloS one, 2021)
OBJECTIVE: Cesarean section (CS) rates are rising rapidly around the world but no conclusive evidence has been obtained about the possible short- and long-term effects of CS on child behavior. We evaluated prospectively the association between CS and infant temperament across the first 9 postpartum months, controlling for indications for CS and investigating parity and infant sex as moderators. METHODS: The sample consisted of mothers and their healthy infants. Infant temperament was measured using the Infant Characteristics Questionnaire completed by the mothers at 6 weeks (n = 452) and 9 months (n = 258) postpartum. Mode of birth was classified into spontaneous vaginal birth (n = 347 for 6 weeks sample; 197 for 9 months sample), CS planned for medical reasons (n = 55; 28) and emergency CS (n = 50; 33). RESULTS: Multiple regression analysis revealed no main effects of birth mode, but showed a significant interaction between birth mode and parity indicating that emergency CS in firstborn infants was associated with more difficult temperament at 6 weeks. There were no significant associations between indications for CS and infant temperament, although breech presentation predicted difficult temperament at 9 months. CONCLUSION: We largely failed to support the association between CS and infant temperament. Although our results suggest that emergency CS may be associated with temperament in firstborns, further research is needed to replicate this finding, preferably using observational measures to assess child temperament.
Keywords: Infant; Humans; Longitudinal Studies; Pregnancy; Breech Presentation; kojenec; poporodní období; Female; temperament; lidé; Temperament; císařský řez; Regression Analysis; parita; vývoj dítěte; ženské pohlaví; longitudinální studie; Child Development; Cesarean Section; Parity; těhotenství; poloha plodu koncem pánevním; matky; prospektivní studie; Postpartum Period; regresní analýza; Mothers; Prospective Studies